A preventive strengthening method for steel columns: Experimental study and numerical analyses. (November 2017) - Lin, Weiwei; Taniguchi, Nozomu; Yoda, Teruhiko
Abstract: Techniques for structural repair and maintenance are becoming increasingly important because of increasing problems associated with aging structures. This paper introduces a method for strengthening aged steel columns by using new construction materials such as glass-fiber-reinforced polymer (GFRP) plates, rapid-hardening concrete, rubber-latex mortar, and reinforcing bars. The purpose of the present study is to investigate the mechanical performance of steel columns before and after strengthening, thereby assessing the effectiveness of the proposed strengthening method. Depending on the possible directions of applied load (major axis or minor axis) and the corrosion conditions, three specimens were employed in the loading tests. Static loading tests were performed on steel columns with and without strengthening. Test results, including load–deflection relationships and the strain development process of the columns, were measured and compared between the original and strengthened columns. Moreover, three-dimensional finite-element models were built to compare the strengthened and original steel columns. Both the experimental and numerical results indicate that the proposed strengthening method can significantly enhance the stiffness in the elastic stage and the load-carrying capacities in the plastic stage, resulting in significant extension of residual service life under real service conditions and improvement of seismic performance during earthquakes. Highlights: A new strengthening method for old steel columns was described. The performance of three steel columns before and after strengthening was investigated. Steel columns under load in different directions and corrosion conditions were learned. Static loading test was performed and the effect of present strengthening method was confirmed. Numerical simulation methods for both original and strengthened columns were studied.